2019
DOI: 10.1111/jam.14526
|View full text |Cite
|
Sign up to set email alerts
|

Microvirgasp. symbiovar mediterranense nodulatesLupinus cosentiniigrown wild in Morocco

Abstract: Aim To analyse the diversity of nodule‐forming bacteria isolated from Lupinus cosentinii naturally grown in the Maamora cork oak forest (Rabat, Morocco). Methods and Results Of the 31 bacterial strains, four were selected based on their REP‐PCR fingerprinting that were studied by sequencing and phylogenetic analysis of their 16S rRNA, gyrB, dnaK, recA and rpoB housekeeping genes as well as the nodC symbiotic gene. The nearly complete 16S rRNA gene sequence of the four representative strains showed that they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The phenotypic analysis showed that all the strains assimilate different carbon sources including glucose, mannose, galactose, and sucrose, while no strain used starch or lactose; this result agrees with previously reported results (Rome et al, 1996;Missbah El Idrissi et al, 2020). Bradyrhizobium canariense BTA-1T does not use sucrose or lactose either (Vinuesa et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The phenotypic analysis showed that all the strains assimilate different carbon sources including glucose, mannose, galactose, and sucrose, while no strain used starch or lactose; this result agrees with previously reported results (Rome et al, 1996;Missbah El Idrissi et al, 2020). Bradyrhizobium canariense BTA-1T does not use sucrose or lactose either (Vinuesa et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…for a long time until Ardley et al (2012) reported the isolation and identification of three symbiotic Microvirga species from L. texensis and Listia angolensis root nodules. More recently, lupines were found to be nodulated by Microvirga strains in Tunisian, Moroccan, and American soils (Beligala et al, 2017;Msaddak et al, 2017Msaddak et al, , 2019Rejili et al, 2019;Missbah El Idrissi et al, 2020). Msaddak et al (2017) suggested that lupines would prefer Bradyrhizobium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the prevalence of slow-growing Bradyrhizobium species, fast-growing bacteria belonging to the genera Phyllobacterium [ 41 , 42 , 71 ], Ochrobactrum [ 27 ], Microvirga [ 42 , 44 , 71 , 84 ], Rhizobium , Neorhizobium, Agrobacterium [ 43 ], and Devosia [ 12 ] have also been described as lupin microsymbionts. Burkholderia , a genus that nodulates other legume species, has also been isolated from L. perennis nodules [ 85 ]; however, its symbiotic effectiveness after re-inoculation has yet to be confirmed.…”
Section: Rhizobia That Nodulate Lupins Many More Than Initially Expectedmentioning
confidence: 99%
“…Until the present century, lupin was assumed to be a microsymbiont-specific legume. However, owing to the evolution of molecular taxonomy, nowadays, lupin can be considered as a promiscuous legume that can be nodulated by different Bradyrhizobium lineages [ 38 , 39 , 40 ], and by bacteria within the genera Phyllobacterium [ 41 , 42 ], Ochrobactrum [ 27 ], Rhizobium, Neorhizobium, Agrobacterium [ 43 ], Microvirga [ 42 , 44 ], and Devosia [ 12 ]. The aim of this review was to collect the existing information on the diversity and taxonomy of the rhizobial bacteria associated with Lupinus spp.…”
Section: Introductionmentioning
confidence: 99%